2008
DOI: 10.1097/01.asw.0000323546.04734.31
|View full text |Cite
|
Sign up to set email alerts
|

Expedited Wound Healing with Noncontact, Low-Frequency Ultrasound Therapy in Chronic Wounds

Abstract: The rate of healing and complete closure of chronic wounds in patients improved significantly when MIST Therapy was combined with standard wound care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 6 publications
1
53
0
2
Order By: Relevance
“…The full complement of scheduled treatments available to patients during the 8 weeks of allocated treatment in the NLFU + SOC and SOC-only arms was 24 and 8, respectively (excluding treatments conducted in the final visit). Following randomisation, NLFU + SOC and SOC-only patients received a median (range) of 23 (20)(21)(22)(23)(24), and 8 (7-8) scheduled treatments during the study, respectively (Table 1). Each application of NLFU had a mean (SD) duration of 3⋅8 (1⋅0) minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full complement of scheduled treatments available to patients during the 8 weeks of allocated treatment in the NLFU + SOC and SOC-only arms was 24 and 8, respectively (excluding treatments conducted in the final visit). Following randomisation, NLFU + SOC and SOC-only patients received a median (range) of 23 (20)(21)(22)(23)(24), and 8 (7-8) scheduled treatments during the study, respectively (Table 1). Each application of NLFU had a mean (SD) duration of 3⋅8 (1⋅0) minutes.…”
Section: Resultsmentioning
confidence: 99%
“…These randomised controlled trials (10,16,17) and several observational studies (mostly retrospective; 12,[19][20][21][22][23] have reported that treatment with NLFU improves wound healing. Kavros reported that significantly more patients with ischaemic wounds treated with NLFU achieved 50% wound closure at 12 weeks compared with those of SOC alone (63% versus 29%; P < 0⋅001).…”
Section: Key Messagesmentioning
confidence: 99%
“…28 This therapy has been shown to be a gentle, painless clinical protocol that is capable of stimulating cells at the wound bed to secrete more growth factors, 29 increase collagen synthesis, reduce inflammation, and induce vasodilation. 28 Although dentistry utilizes similar technologies routinely in debridement and disinfection of periodontal defects, there has been limited direct exploration of its utility in oral soft tissue healing. phatics, leading to improved wound healing.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Procedural guidance as in central line placement [24,25], diagnostic assessment as in the Focused Assessment with Sonography in Trauma (FAST) [26][27][28], thoracic cavitary ultrasonography to assess for pleural effusion, pneumothorax, or pneumonia [29,30], verification of tracheal airway placement [18], musculoskeletal diagnosis and treatment [14], cardiovascular applications [11,12,31], and gynecological screening [32,33] are now all commonplace in the clinical arena. New applications of ultrasound are presently being explored in the realms of thermal tumor ablation, hemorrhage control, nanotechnology, fracture healing, and noncontact wound therapy [34][35][36][37][38][39].…”
Section: Overview Of General Ultrasound Applications In Hemodynamic Amentioning
confidence: 99%